Comparing Emergency Medical Services Processing Times for Stroke Patients Before and During COVID-19 Pandemic; A Cross-sectional Study - Huabbangyang, Thongpitak; Klaiangthong, Rossakorn; Prasittichok, Krit; Koikhunthod, Sutida; Wanna, Jakkapan; Sudajun, Nutthapong; Khaisri, Parichat; Kamsom, Anucha (Archives of Academic Emergency Medicine, 2022)
Introduction: Coronavirus disease 2019 (COVID-19) has directly affected global healthcare, especially the front-line of healthcare provision, including emergency medical services (EMS). The present study aimed to compare EMS processing times and the number of acute stroke patients serviced by EMS before and during COVID-19 pandemic. Methods: This is a retrospective observational review of Bangkok Surgico Medical Ambulance and Rescue Team (S.M.A.R.T.) EMS data from 2018 to 2021. The EMS processing times and the number of acute strokes were compared between pre-COVID-19 era (January 1st, 2018, and December 31st, 2019) and during COVID-19 pandemic (January 1st, 2020, and December 31st, 2021). Results: The number of stroke patients transported by EMS in one year, before and during COVID-19 pandemic was 128 and 150 cases, respectively (Change difference = 17.2%, 95% CI: 11.1–24.9). However, the average number of acute stroke patients per week was not significantly different (p = 0.386). The mean total EMS processing times before and during COVID-19 era were 25.59 ± 11.12 and 45.47 ± 14.61 minutes, respectively (mean difference of 19.88 (95% CI: 16.77–22.99) minutes; p < 0.001). The mean time from symptom onset to EMS arrival (p < 0.001), the mean call time (p < 0.001), the mean response time (p < 0.001), and the mean scene time (p < 0.001) were significantly higher during COVID-19 period. The mean transportation times for stroke patients was similar before and during COVID-19 pandemic (10.14 ± 6.28 and 9.41 ± 6.31 minutes, respectively; p = 0.338). Conclusions: During COVID-19 pandemic, the number of acute stroke patients serviced by EMS increased substantially, but there was no difference in the average number of patients per week. During the pandemic, EMS processing times markedly increased.